Role of PSA in Diagnosis of Chronic Prostatitis - Yasir Abdulateef (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Prostatitis is the poor cousin of prostatic cancer and Benign hyperplasia. The prevalence of prostatitis in general population was estimated to be 0.5 to 14.2% in developed countries. Publishing in Iraq was concern mainly with treatment of prostatitis.Objective: This work was carried out to comment on the concept of prostatitis in clinical practice.Method: A total of 275 males was included in this study. They were complaining of urinary symptoms (frequency, urgency, hesitancy, straining, difficulty in initiation urinary stream).All cases were confirmed to have chronic prostatic after excluding prostatic carcinoma by abdominal ultrasound, free to total PSA and urinary Prostatic carcino-antigen-3. Their age was 45.6 ± 9.6 year. Urine samples were proceeded immediately after collection. Centrifuged and non-centrifuged specimen were examined.Results: PSA was affected significantly by age (p = 0.002). A significant high level was observed among those complaining of pain during ejaculation (p = 0.0001).Those showed epithelial cells in urine had significant high level of PSA (p = 0.0001). Uric acid in urine was associated with significant high level of PSA (p = 0,03).Conclusion: The diagnosis of CP / CPPS might be outside the traditional urologic practice and might consider PSA level too.